School Education and the Transformation of Traditional Knowledge Structures in Late Qing China: A Focus on Curriculum Design (Journal of Advanced Research in Social Sciences, 2025)
The late Qing period (1840-1912) was a significant era of transition for Chinese society from traditional to modern forms. Following the Opium Wars, when the Qing government was compelled to pay indemnities and open treaty ports, the influx of Western natural sciences impacted China, disrupting the Confucian ethical and moral foundations that shaped the traditional academic structures of late Qing China. Under the influence of the eastward transmission of Western learning, China’s traditional knowledge structure—long centered on Confucian classics and historical texts—was reshaped and diversified as Western disciplinary systems, introduced through new schools, brought new subjects and methods. This study analyzes historical documents on the late Qing school curricula to examine how educational subjects were used to organized and classified Chinese and Western knowledge. It further investigates the evolution of discipline-centered education within modern academies and traces the broader transformation of China’s knowledge structure, ultimately revealing how it gradually integrated into the modern epistemic system.